Liver Involvement in Patients with Systemic Sclerosis: Role of Transient Elastography in the Assessment of Hepatic Fibrosis and Steatosis - Giovanna Cuomo; Carlo Iandoli; Raffaele Galiero; Alfredo Caturano; Claudio Di Vico; Danilo Perretta; Pier Vincenzo Adamo; Roberta Ferrara; Luca Rinaldi; Ciro Romano; Ferdinando Carlo Sasso (Diagnostics, 2023)
Background Systemic sclerosis (SSc) is a rare, multisystemic disorder of connective tissue characterized by widespread inflammation, vascular abnormalities, and both skin and visceral organ fibrosis. Tissue fibrosis is the final phase of a complex biological process of immune activation and vascular damage. Objectives The aim of the study was to assess hepatic fibrosis and steatosis in SSc patients by transient elastography (TE). Methods Fifty-nine SSc patients fulfilling the 2013 ACR/EULAR classification criteria were recruited. Clinical and laboratory findings, modified Rodnan skin score (mRSS), activity index, videocapillaroscopy, echocardiography, and lung function data were analyzed. Liver stiffness (LS) was measured by transient elastography (TE), with 7 kPa used as the cut-off value for significant liver fibrosis. In addition, hepatic steatosis was evaluated by means of controlled attenuation parameter (CAP) findings. Specifically, CAP values ≥ 238 ≤ 259 dB/m were considered consistent with mild steatosis (S1), values ≥ 260 ≤ 290 dB/m were compatible with moderate steatosis (S2), and values ≥ 291 dB/m were indicative of severe steatosis (S3). Results The median age of patients was 51 years, with a median disease duration of 6 years. The median LS was 4.5 (2.9–8.3) kPa; 69.5% of patients had no evidence of fibrosis (F0); 27.1% displayed LS values between 5.2 and 7 kPa; and only 3.4% of patients had LS values > 7 kPa (F3). The median CAP value for liver steatosis was 223 dB/m (IQR: 164–343). Overall, 66.1% of patients did not show evidence of steatosis (CAP values < 238 dB/m); 15.2% showed values consistent with mild (S1) steatosis (CAP value ≥ 238 ≤ 259 dB/m); 13.5% had moderate (S2) steatosis (CAP value ≥ 260 ≤ 290 dB/m); and 5.1% were deemed to have severe steatosis (S3) due to CAP values ≥ 291 dB/m. Conclusions Although systemic sclerosis is associated with fibrosis of the skin and several organs, only 3.4% of our patient population showed evidence of marked liver fibrosis, which is the same prevalence as that expected in the general population. Therefore, fibrosis of the liver did not appear to be a significant concern in SSc patients, albeit moderate fibrosis could still be detected in a significant proportion of subjects. A prolonged follow-up may clarify whether liver fibrosis in SSc patients may still progress. Likewise, the prevalence of significant steatosis was low (5.1%) and depended on the same variables associated with fatty liver disease in the general population. TE was shown to be an easy and valuable method for detection and screening of hepatic fibrosis in SSc patients with no additional risk factors for liver disease and may be useful to assess the potential progression of liver fibrosis over time.